(untitled) (Fiep Bulletin - online, 2012)
The objective of this research was to investigate the physical development of male students of 7th and 8th grades. The study group was composed by 28 students aged between 12 and 18 years of Maria Ilha Baisch High School in the municipality of Dona Francisca-RS, Brazil. The following physical tests were used: horizontal jump, throwing the 150g ball, bending over in 1 minute, high fixed bar, 60 and 1500 meters run, based on the standards of assessment of the Russian school of the students physical development. Anthropometric measurements were also collected: weight, height and BMI. The survey results showed that male students have regular physical development. We think this happens because there are no targets for physical education teachers to follow, targets that require the development of these physical abilities of the students, in order to strength their health, through their physical development.